A CsrA/RsmA translational regulator gene encoded in the replication region of a Sinorhizobium meliloti cryptic plasmid complements Pseudomonas fluorescens rsmA/E mutants - Agaras, Betina Cecilia (2012)
Members of the CsrA/RsmA family are global regulatory proteins that bind to mRNAs, usually at the ribosome-binding site, to control mRNA translation and stability. Their activity is counteracted by small non-coding RNAs (sRNAs), which offer several binding sites to compete with mRNA binding. The csrA/rsmA genes are widespread in prokaryotic chromosomes, although certain phylogenetic groups such as Alphaproteobacteria lack this type of global regulator. Interestingly, a csrA/rsmA-like sequence was identified in the replication region of plasmid pMBA19a from the alphaproteobacterium Sinorhizobium meliloti. This rsmA-like allele (rsmASm ) is 58 % identical to Xanthomonas axonopodis pv. citri chromosomal rsmA and bears an unusual C-terminal extension that may fold into an extra α-helix. Homology-based modelling of RsmA Sm suggests that all key mRNA-binding residues are conserved and correctly positioned in the RNA-binding pocket. In fact, a 1.6 kb fragment from pMBA19a encompassing the rsmASm locus restored rsmA/E-dependent phenotypes of rsmA/E gacS Pseudomonas fluorescens mutants. The functionality of RsmA Sm was confirmed by the gain of control over target aprA′–′lacZ and hcnA′–′lacZ translational fusions in the same mutant background. The RsmA Sm activity correlated with Western blot detection of the polypeptide. Phenotype and translational fusion data from rsmA/E P. fluorescens mutants expressing RsmX/Y/Z RNAs indicated that RsmA Sm is able to bind these antagonistic sRNAs. In agreement with the latter observation, it was also found that the sRNA RsmY was stabilized by RsmA Sm . Deletion of the C-terminal extra α-helix of RsmA Sm affected its cellular concentration, but increased its relative RNA-binding activity. This is believed to be the first report of the presence and characterization of a functional csrA/rsmA homologue in a mobile genetic element.